FAKTOR-FAKTOR YANG MEMPENGARUHI REPURCHASE INTENTION PADA LIVE STREAMING SHOPPING: STUDI TERHADAP GENERASI Z DI INDONESIA - Tirtayani, I Gusti Ayu; Wedhana Purba, Ida Bagus Gde Indra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2024)
This research aims to analyze the influence of Interaction Quality on repurchase intention with trust as a partial mediating variable in the context of e-commerce live streaming. This research uses a quantitative approach by collecting data from 331 respondents who are part of generation Z in Indonesia. The data collection method was carried out through an online survey, and data analysis used path analysis techniques to test the relationship between variables. The research results show that Interaction Quality has a positive and significant influence on repurchase intentions. In addition, trust was shown to act as a significant mediating variable in the relationship between Interaction Quality and repurchase intention. These findings emphasize the importance of sellers not only focusing on the technical and informative aspects of interactions, but also on building and maintaining consumer trust. Thus, this research makes a significant contribution to digital marketing literature and offers practical insights for e-commerce players in increasing customer loyalty among generation Z in Indonesia.